The Dual Role of miR-186 in Cancers: Oncomir Battling With Tumor Suppressor miRNA - Xiang, Ying; Tian, Qing; Guan, Li; Niu, Shuai-shuai (Frontiers in Oncology, 2020)
MicroRNAs (miRNAs) are a class of noncoding RNAs in short length which regulate genes expression at post-transcriptional level. Alterations of miR-186 expression were demonstrated in numerous cancers, playing a vital role in oncogenesis, invasion, metastasis, apoptosis and drug resistance. MiR-186 was documented as a tumor suppressor miRNA in the majority of studies, while conflicting reports verified miR-186 as an oncomir. The contradictory role in cancers may impede the application of miR-186 as a diagnostic and therapeutic target, as well as other dual functional miRNAs. This review emphasizes the alterations and functions of miR-186 in cancers, and discuss the mechanisms behind the contradictory findings. Among these, targets abundance and dose-dependent effects of miR-186 are highlighted. It is aimed to remind of challenges in developing diagnostic and therapeutic strategies for cancer treatment based on dual functional miRNAs.